2020
DOI: 10.2298/sos2002219i
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the concentration of alkaline activator and aging time on the structure of metakaolin based geopolymer

Abstract: This paper outlines the production of an inorganic polymer/geopolymer using a metakaolin by an environmental friendly, energy saving, clean technology to conserve natural environment and resources. The influence of alkali activation, i.e. different concentration of NaOH as a component of alkali activator mixture on the process of geopolymerization of metakaolin is investigated. Also, process of aging time of geopolymer is followed by several analytical methods. The structure of metakaolin and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 22 publications
0
19
0
Order By: Relevance
“…Hence, ash compositions vary over a wide range. The most important development in the field of coal combustion products (CCP) utilization in Europe in 2004 was the approval of a revised European standard on fly ash for concrete [1][2][3][4][5][6][7][8]. The standard covers siliceous fly ash and includes for the first time fly ash obtained from co-combustion of coal and certain cocombustion materials.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hence, ash compositions vary over a wide range. The most important development in the field of coal combustion products (CCP) utilization in Europe in 2004 was the approval of a revised European standard on fly ash for concrete [1][2][3][4][5][6][7][8]. The standard covers siliceous fly ash and includes for the first time fly ash obtained from co-combustion of coal and certain cocombustion materials.…”
Section: Introductionmentioning
confidence: 99%
“…The new standard introduces a quality control system for fly ash, consisting of an internal quality control by the producer and an audit testing by a certification body which is notified by the building authorities. The European Union has approved the use of fly-ash derived from the co-combustion of coal with wood, straw, olive husks, green wood, cultivated biomass, animal meal, municipal solid waste and paper sludge as a cement admixture, as long as the fly-ash contains less than 5 wt % carbon, 5 wt % total alkali, and 0.1 wt % chloride [7][8][9][10][11][12][13][14][15]. Finding means of utilizing waste products is a very important and actual field of research.…”
Section: Introductionmentioning
confidence: 99%
“…XPS analysis was performed using a SPECS instrument for detailed chemical composition characterization using X-ray-induced photoelectron spectroscopy. More detailed explanation can be found in Nenadovic et al, 2017 [ 31 ] and Ivanovic et al, 2020 [ 33 ]. Photoelectron emission was excited by monochromatic Al Kα line with photon energy of 1486.67 eV.…”
Section: Methodsmentioning
confidence: 99%
“…It was confirmed that, with the knowledge of thermodynamic parameters, there is a better understanding of the first phase of gel formation of geopolymer structure. In previous research by Nenadović et al [ 31 ], Kljajević et al [ 32 ] and Ivanović et al [ 33 ], the synthesis and structure of geopolymer material, the influence of aluminosilicate matrix and alkali activator change were monitored. Materials with 12 M NaOH are the most common subjects, so the aim of this study is to examine the effect of Nd and Sm in the form of oxide incorporation in the first phase of gelation of the geopolymer structure.…”
Section: Introductionmentioning
confidence: 99%
“…The variation reveals a polycondensation reaction, characteristic of the formation of a specific network, and might point to the formation into a complete three-dimensional network. The bands in the range of 850-600 cm −1 are related to the ring vibrations of the Si-O bonds of the silicate network [60,61], and the Al-O stretching vibrations might be the bending mode of AlO 6 octahedra [62][63][64].…”
Section: Ftirmentioning
confidence: 99%